Virus infections and chronic fatigue in athletes: Is there a link? - Madeley, C. R. (International SportMed Journal, 2000)
Viruses are frequently blamed for a fall (often sudden) in athletic performance. This does not only affect the élite, but athletes at all levels. Although common sense suggests that in some cases a virus that spreads systemically could be involved, there is a serious lack of any corroborative hard evidence. Because viral infections are very common and mostly trivial, only a well-constructed prospective study can establish beyond doubt the role of viruses in longer-term sequelae. This review attempts to explain why this is so, and discusses the major practical problems that will be encountered by anyone trying to collect such hard data. The study will have to be comprehensive, is likely to encounter ethical questions, may not produce any positive results, and will be expensive.